Beneficial modulation of the tumor microenvironment and generation of anti-tumor responses by TLR9 agonist lefitolimod alone and in combination with checkpoint inhibitors. (2nd December 2019) - Kapp, Kerstin; Volz, Barbara; Oswald, Detlef; Wittig, Burghardt; Baumann, Matthias; Schmidt, Manuel
ABSTRACT: Activation of Toll-like receptor 9 (TLR9) is known to foster innate and adaptive immune responses and thus improve immune-mediated control of malignant disease. Lefitolimod is a potent TLR9 agonist without chemical modification developed for immunotherapeutic strategies. Modulation of the tumor microenvironment (TME) is a crucial requirement for the response to various immunotherapies: Immunogenic ("hot") tumors, characterized by their T cell-infiltrated TME, respond better compared to non-immunogenic ("cold") tumors. It has been speculated that the mode-of-action of lefitolimod provides the necessary signals for activation of immune cells, their differentiation into anti-tumor effector cells and their recruitment into the TME. We investigated the effect of lefitolimod on TME, and its potency to induce synergistic anti-tumor effects when combined with immune checkpoint inhibitory antibodies (CPI) in a murine model. Indeed, we could show that treatment with single-agent lefitolimod beneficially modulated the TME, via infiltration of activated CD8+ cells and a shift in the macrophage population toward M1 phenotype. The result was a pronounced anti-tumor effect correlated with the magnitude of infiltrated immune cells and tumor-specific T cell responses. In line with this, lefitolimod led to persistent anti-tumor memory in the EMT-6 model after tumor re-challenge. This was accompanied by an increase of tumor-specific T cell responses and cross-reactivity against different tumor cells. Lefitolimod clearly augmented the limited anti-tumor effect of the CPI anti-PD1 in an A20 and anti-PD-L1 in a CT26 model. These properties of potent immune surveillance reactivation render lefitolimod an ideal candidate as therapeutic agent for immuno-oncology, e.g. improving CPI strategies.